Crossbar array of selector-less TaOx/TiO2 bilayer RRAM. Issue 11 (November 2015) - Chou, Chun-Tse; Hudec, Boris; Hsu, Chung-Wei; Lai, Wei-Li; Chang, Chih-Cheng; Hou, Tuo-Hung
Graphical abstract: Abstract: In this work, we have implemented self-rectifying TaO x /TiO2 RRAM in a selector-less 6 × 6 crossbar array with various desiring features, including: (1) simple fabrication using only three masks, (2) high self-rectifying ratio up to 10 3 for sneak current suppression, (3) stable bipolar resistive-switching characteristics without the need for electro-forming and current compliance, (4) data retention time over 10 4 s, and (5) robust READ and WRITE disturb immunity. Finally, an achievable array size of 1 Mb was simulated using an All-LPU read scheme and a V/3 write scheme.